A Review of Pancreatico-Pleural Fistula in Pancreatitis and Its Management - Burgess, N. A. (Hindawi Publishing Corporation, 1992)
Pancreatico-pleural fistula is a rare condition in which pancreatic enzymes drain directly in to the pleural cavity, most commonly from an enlarging pseudocyst. We review the literature on the causes, investigations and treatment of pancreatico-pleural fistulae and compare this with our own experience of the case of a 41 year old man with a left sided pancreatico-pleural fistula associated with pancreatic duct obstruction. The fistula could not be demonstrated by USS, CT or ERCP, and after these investigations the patient was managed conservatively. However, deterioration in the patients' condition led to an urgent but not emergency laparotomy and operative pancreatogram. This demonstrated the distally obstructed pancreatic duct, with associated pleural fistula for which aggressive surgical intervention was indicated. The patient subsequently completely recovered.